Cartografia tátil: política inclusiva para estudantes com deficiência visual na educação superior - Sehnem, Cristian Evandro (2018)
As there is an increasing number of disabled students in Higher Education, changes in technical and pedagogical subsidies that guarantee their teaching and learning process are pivotal. For visually impaired students, mobility on campus and access to visual images used in class, such as maps, graphs, and drawings, which are adapted in order to allow these students to reach, explore and understand their characteristics in the most autonomous and independent way, are probably one of the main inaccessibilities that must be overcome. Thus, the present qualitative and applied research aims to get to know aspects of tactile cartography and its usability for visually impaired students in their teaching and learning process in Higher Education. In order to do so, data was collected from interviews with six visually impaired university students and the results were categorized by means of content analysis, under the motto “Nothing about us, without us (Nada sobre nós, sem nós)” as the author himself is visually impaired. Although tactile cartography resources are little-known and not commonly found in Higher Education, they provide students with several different possibilities and benefits in their learning process, mobility, social interaction, and education, which would be even greater under different circumstances. Even when embossed materials were made available mainly in Basic Education, matters of usability did not allow students to fully reach a rational understanding which could be continued and perfected later on. However, the importance given to a teaching methodology that guides and accompanies this exploration and learning from tactile resources from a non-visual perspective was unanimous. From these facts one may conclude that visually impaired students can easily construct mental images of visual elements when tactile cartography resources are combined with sufficient three-dimensional features and with an appropriate teaching methodology. Furthermore, it is high time new ways of designing and making these resources with three-dimensional printers with higher quality, durability, and portability were adopted. Therefore, the product elaborated in this research offers an initial contribution to a technical norm on tactile cartography from the perspective of an inclusive teaching and learning process.